Analysis Of The Financial Management Performance Of Legal Entity State Universities (Case Study At Universitas Negeri Semarang) - Firmansyah, Riza; Hartono, Rudi; Farliana, Nina (Politeknik Raflesia Press, 2024)
The purpose of this research is to determine the influence of human resource quality, organizational commitment, and facilities and infrastructure on financial management performance. This research also aims to test the relationship of the financial information system as a moderating variable on the influence of human resource quality, organizational commitment, and facilities and infrastructure on financial management performance. The sample used in this study amounts to 90 people involved in the financial management process at UNNES. The data analysis technique used is SmartPLS 3.3.3 software. The results of the study show that human resource quality and organizational commitment positively influence financial management performance. In contrast, facilities and infrastructure do not affect financial management performance. The moderation test results of the financial information system strengthen the relationship between human resource quality and financial management performance. However, the relationship between organizational commitment and facilities and infrastructure cannot be moderated by the financial information system.